Cultura escolar e ensino de História em tempos de Ditadura Militar no Instituto de Educação Gastão Guimarães (Feira de Santana – BA, 1968- 1978) - Barros, Dulcinea Cerqueira Coutinho (2015)
This work is the result of a research that investigated the school culture and the teaching of history developed at the Institute of Education Gastão Guimarães (IEGG) in the context of the Brazilian Military Dictatorship, more emphatically in the years 1968-1978, times of student struggles, the “economic miracle”, reforms in higher education and 1st and 2nd degree and, among others, the duration of the Institutional Act No. 5 (AI-5). In general, educational institutions, their cultures and history teaching they developed suffered the effects of the military dictatorship installed in the country. However, there are few studies that question so localized impact and interference in the subject, knowledge and of history teaching practices among the traditions, regularities and “continuísmos” that permeate the school culture. This was the general objective chased in the research that focused on the IEGG, a public school for primary teachers installed since 1927, in Feira de Santana, Bahia. Therefore, I used the theoretical and methodological propositions enabled by the analytical category School Culture (JULIA, 2001; Frago, 2007), which demanded as documentary sources for the research, educational and administrative characterized writings that belong to the school’s files, oral and photographic memories from former teachers and former students and teaching materials used by these subjects at the school. The analysis of the sources, their confrontation with the education legislation, with periodic sources and also with a specialized bibliography allowed the discussion in this paper about the process imposition of dictatorship and its memory in Brazil and in Feira de Santana; placing the constitution process of a focused educational institution, its school culture, the main subjects and importance to the city and, finally, the teaching of history, the knowledge and practices they developed there. This, in general, has been permeated by a surveillance and fear spectrum, prevailing between their knowledge and practices the exalting official memory made by political and representative historical figures of sacrifice for the nation, civic and patriotic rituals carried out in partnership with other school subjects and also “techniques” that, in that context, renewed the methodological aspects of history teaching, without, however, renewing its contents.